Pulmonary Disease due to Mycobacterium malmoense in British Columbia - Mohamed S Al-Moamary; William Black; Kevin Elwood (Canadian Respiratory Journal)
Mycobacterium malmoense was first described in northern Europe and the United Kingdom in 1977. Since then, reports have appeared with increasing frequency. Cases have, however, rarely been reported from the United States, and, until now, none have been reported in Canada. This may reflect either true low prevalence of the disease or underdiagnosis by laboratories due to slow growth of the organism. This report describes a case of pulmonary disease caused by M malmoense in a 44-year-old man from British Columbia who was successfully treated with an 18-month course of conventional antituberculous drugs combined with a macrolide. This is the first report of this disease in British Columbia and, to our knowledge, in Canada.